KAJIAN SOSIOLOGIS TENTANG FENOMENA PERILAKU MEROKOK SISWA DI MADRASAH TSANAWIYAH AL - AMIN TABANAN - Ningrum, Ayu Satria; Punia, I Nengah; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT Interaction of adolescents with their social environment is very influential in the formation of adolescent identity. Smoking behavior of students in Madrasah Tsanawiyah Al-Amin occurs because of social interaction with family environment, peers, and school. The purpose of this study was to find out the reasons students do smoking behavior as well as to determine the impact of smoking behavior of students. In the process will also described the beginning of students try tobacco from the point of view of internal factors and external factors. Charles Horton Cooley's Self-Looking Theory of Glass is used to analyze smoking behavior in students, using descriptive qualitative research methods. The result of this research is the influence of smoking behavior from family environment, peers, and school. In addition, there are three impacts of smoking behavior of Madrasah Tsanawiyah Al-Amin students, among others: (1). Social Impact, (2). Health, (3). Economics. Keywords: Teenagers, Students, Smoking Behavior